PENGARUH BUDAYA ORGANISASI TERHADAP MUTU PELAYANAN PROGRAM PEMBANGUNAN DI BAPPPPEDA KABUPATEN SUMEDANG - Indra Wahyudinata; Basarudin; Devitka Serin Indrianto; Devy Amalia Hidayati; Rika Fauzi Astuti; Yoga Daswara (LPPM UNSAP & FISIP UNSAP, 2020)
The research objective of the researcher is to find out the Organizational Culture and Service Quality of the Development Program, to find out the relationship between Organizational Culture and the Quality of Development Program Services and to find out the magnitude of the influence of Organizational Culture on Service Quality in in BAPPPPEDA Sumedang Regency.The method used in this study is a quantitative research method which is used in research based on the philosophy of positivism in order to test the hypotheses that have been set. And the type of statistics used is inferential sampling technique used in this study is the Simple Random Sampling technique, with a population of 80 people then researchers used the Slovin formula to obtain a sample of 44 respondents. The analysis used includes the calculation of percentages, correlation tests, normality tests, significance tests, and coefficient of determination tests.Based on the results of the study, researchers can describe that the organizational culture in BAPPPPEDA Sumedang Regency is in very good criteria with the results of the analysis reaching 84.54%. Likewise, the quality of development program services in BAPPPPEDA in Sumedang Regency is in very good criteria with an analysis reaching 86.33%. From the correlation analysis, the correlation value is 0.419, which indicates a positive and significant relationship between Organizational Culture and Service Program Development Quality. While the influence of organizational culture on the quality of development program services in BAPPPPEDA in Sumedang Regency reached 17.6%, the remaining 82.4% was influenced by other factors not examined by researchers called epsilon factor.